The nurse and the humaninzing approach in nursing care during labor - Isolda Pereira da Silveira; Ana Fátima Carvalho Fernandes (Rev Rene)
The aim of this study is to identify the nursing care given to the laboring parturients based on the nurse’s perceptions under humanitarian views. five nurses, who work during morning, evening and night shifts at the normal delivery unit, were the basis of this study. the data were collected during the months of july and august 2002 in a public federal maternity. for data collection it was conducted open observation and recorded interviews. the data analysis was supported by bardin’s framework and also by paterson and zderad’s humanistic theory. we concluded, through this study, that nurses believe to be necessary to reorganize the service and change the attitude before birth. we suggest better professional preparation to empower the nursing humanized care for laboring parturients and the authentic presence of the nurse during delivery.